1999
DOI: 10.1002/1531-8257(199911)14:6<972::aid-mds1010>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA damage in the aging mouse brain

Abstract: The brain exhibits regional vulnerabilities to many insults, and age itself has differential effects on neuronal populations as exemplified by the age‐dependent loss of dopaminergic neurons in the nigrostriatal system. We hypothesized that oxidative damage to DNA was more likely to occur in the nigrostriatal system which undergoes significant neurochemical and functional changes with age. To test this hypothesis, oxidative damage to DNA, indicated by levels of 8‐hydroxy‐2′‐deoxyguanosine (oxo8dG), was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 26 publications
3
50
2
Order By: Relevance
“…These results indicate that aging is coupled to an increase in cerebellar oxidative damage for a broad array of molecules. In confirmation of previous work, aging was associated with an increase in cerebellar markers of lipid [21] and DNA oxidation [4,8,30]. In addition, the currents study provides the first evidence that RNA oxidation increases in the cerebellum with advanced age.…”
Section: Discussionsupporting
confidence: 91%
“…These results indicate that aging is coupled to an increase in cerebellar oxidative damage for a broad array of molecules. In confirmation of previous work, aging was associated with an increase in cerebellar markers of lipid [21] and DNA oxidation [4,8,30]. In addition, the currents study provides the first evidence that RNA oxidation increases in the cerebellum with advanced age.…”
Section: Discussionsupporting
confidence: 91%
“…Lu et al [23] found that oxidative DNA damage accumulates preferentially in the promoter regions of several genes involved in synaptic plasticity, vesicular transport, and mitochondrial function. A differential accumulation of oxidative DNA lesions among brain regions has also been reported, suggesting that some areas of the brain are more prone to oxidative DNA modifications than others [110,111].…”
Section: Dna Oxidation and Accumulation In Alzheimer Diseasementioning
confidence: 94%
“…The sequences and descriptions of the oligonucleotides used are shown in Table 1. DNA markers were identical to the CAG repeat-containing substrates, except they were damagefree; they corresponded to 100-nucleotide (CAG) 20 , 115-nucleotide (CAG) 25 , and 130-nucleotide (CAG) 30 . The markers were synthesized and PAGE-purified by Integrated DNA Technologies.…”
Section: Methodsmentioning
confidence: 99%
“…Although mismatch repair proteins have been shown to be essential for CAG repeat expansion (17,28), this repair pathway does not appear to account for the aging-dependence of the repeat expansion. Because aging is considered to involve increased oxidative stress (29,30), it is reasonable to suggest that the age-dependent neuronal CAG repeat expansion involves oxidative DNA damage (27,31). Indeed, a linkage between the repeat expansion in brain and oxidative DNA damage was established in a recent study (25).…”
Section: Trinucleotide Repeat (Tnr)mentioning
confidence: 99%